TOKOH FALAK MINANGKABAU (STUDI PEMIKIRAN SAADOEDDIN DJAMBEK DAN TAHIR JALALUDDIN) - Hendri Hendri; Fajrul Wadi; Saiful Amin; Andriyaldi Andriyaldi; Fahmil Samiran (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
This paper talks about the contribution of the Minangkabau Falak figures about dawn in Indonesia. At this time of dawn in Indonesia which is used as a reference or guideline of the Ministry of Religion that is the result of the thoughts and ijtihad of the previous scholars who are still in use today for the height and position of the sun at the time of the dawn of Sadiq -200. The clerics and celestial figures who be ijtihad about dawn with the -200 position came from Minangkabau namely Saadoeddin Djambek which is famous for the books of prayer and fasting in the polar regions. Saadoeddin djambek set -200 by quoting the opinion of his teacher, Sheikh Muhammad Tahir Jalaluddin al-Minangkabawi about determining the prayer time in Pati Kiraan and Nukhbah at-Taqrîrât fîHisâb al-Auqât was Samt al-Qiblah bi al-Lughâritmât. Determination of the height of the sun at the -200 position is based on geographical observations and considerations due to the factor of Indonesia that is close to the equator and influenced by astronomical data used, solar height and its correction as well as the determination of latitude and longitude.